ASPEK LINGUISTIK DAN MAKNA PEMBELAJARAN PADA PUISI KARYA D. ZAWAWI IMRON - Izzah, Ismatul; Mintowati, Maria; Mulyono (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
The linguistic study of D. Zawawi Imron's poetry provides a lot of inspiration from each work that can be known by the wider community. The purpose of this study is to find out the influence of semantic aspects in the form of phonology, range, metaphor, and diction of D. Zawawi Imron's poetry works that have been published and circulated in the community. For the research method used in semantic studies, we need to adopt an approach that focuses on meaning, both lexically (literal sense) and contextually (meaning that develops in the context of poetry). Semantics in the study of poetry is not only about understanding the meaning of words, but also how that meaning is shaped by the context, structure, and choice of language used by the poet to convey the message. The result of this study is to determine the influence of word choice diction, metaphor, and phonology from D. Zawawi Imron's poetry works which can be studied in analyzing word choice in literary works that will be analyzed and reveal the meaning of the connotation and diction of the language that has been chosen. .